WEB SERVICE SEBAGAI SOLUSI INTEGRASI DATA PADA SISTEM INFORMASI AKADEMIK UNIVERSITAS BINA DARMA - Purnamasari, Susan Dian (JURNAL ILMIAH MATRIK, 2012)
Web service was the new paradigm in implementation the distributed system went through web that used the basis of XML technology, XML is a markup languange which represents document that is exchanged via internet. With exact structure and definition, XML can be used for representation and communication of distributed relational database. This research focusses on database representation and synchronization between relational databases. Bina Darma University has of Education Office is spread and separated by distance which will make the distribution of data in terms of student is not very effective and efficient. Online distribution also does not help because it has to moved from one site to another to retrieve the data. This study aims to build a web services technology that is capable to integrating the data in the Bina Darma University. With take advantage of XML, the integration of data from Bina Darma university which have different databases can be done. Keywords: Web Services, Data Integration, XML